2018
DOI: 10.1080/21663831.2018.1443978
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of α-, β-, and ϵ-phases of Ga2O3 using MOCVD and HVPE techniques

Abstract: Heteroepitaxial films of Ga 2 O 3 were grown on c-plane sapphire (0001). The stable phase β-Ga 2 O 3 was grown using the metalorganic chemical vapor deposition technique, regardless of precursor flow rates, at temperatures between 500 • C and 850 • C. Metastable α-and ε-phases were grown when using the halide vapor phase epitaxy (HVPE) technique, at growth temperatures between 650 • C and 850 • C, both separately and in combination. XTEM revealed the better lattice-matched α-phase growing semi-coherently on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
109
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 34 publications
(33 reference statements)
10
109
2
1
Order By: Relevance
“…In recent years, high quality a-Ga 2 O 3 epilayers and heterostructures have been realized on sapphire substrates by mist-CVD 6 and halide vapor phase epitaxy (HVPE). [10][11][12] Consequently, vertical Schottky diodes with a low on-resistance of 0.4 mX cm 2 and a breakdown voltage of 855 V have been reported. 13 Due to the large in-plane lattice mismatch of about 4.81%, a-Ga 2 O 3 epilayers deposited on sapphire substrates typically result in a high density of dislocations of the order of 10 10 cm À2 .…”
mentioning
confidence: 99%
“…In recent years, high quality a-Ga 2 O 3 epilayers and heterostructures have been realized on sapphire substrates by mist-CVD 6 and halide vapor phase epitaxy (HVPE). [10][11][12] Consequently, vertical Schottky diodes with a low on-resistance of 0.4 mX cm 2 and a breakdown voltage of 855 V have been reported. 13 Due to the large in-plane lattice mismatch of about 4.81%, a-Ga 2 O 3 epilayers deposited on sapphire substrates typically result in a high density of dislocations of the order of 10 10 cm À2 .…”
mentioning
confidence: 99%
“…It should be noted that α ‐Ga 2 O 3 might also be observed at the interface with sapphire . Phase stabilization of α ‐Ga 2 O 3 was observed on r ‐plane α ‐Al 2 O 3 in plasma‐assisted MBE up to a film thickness of around 200 nm .…”
Section: Resultsmentioning
confidence: 92%
“…Gallium oxide (α, β, and ε‐Ga 2 O 3 ) possesses excellent optical properties and its simpler synthesis methods pave the way for large scale production. [ 6–8 ] Recently, the 2D Ga 2 O 3 from bulk β‐Ga 2 O 3 , a new member of 2D material group, obtained by mechanical exfoliation and chemical synthesis has ignited a new round of research, and its optoelectronic properties are gradually revealed. [ 9,10 ] The field effect transistors (FETs) based on 2D β‐Ga 2 O 3 materials showed a large drain current density and a reduced contact resistance.…”
Section: Introductionmentioning
confidence: 99%